Strategi Pemasaran Digital untuk Meningkatkan Penjualan pada UMKM Tahu Sumedang Bang Amir Kec. Medan Denai, Kota Medan - Linda Lenta Sari Sihombing; Reza Fahrezi; Mahesa Rani Hasibuan; Mhd Zul Azri (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The analysis in this study focuses on the digital marketing strategy implemented by the UMKM Tahu Sumedang Bang Amir located in Medan Denai District and aims to measure the extent of the increase in sales. This study is qualitative and descriptive technical using data collection methods conducted through interviews, observations, and document analysis. The distribution and increase in sales of Tahu Sumedang Bang Amir, this study, by utilizing digital marketing, including using social media, delivery applications, and Google Maps services, can be helped. Based on the data analysis, this study, the manager of the UMKM Tahu Sumedang Bang Amir, experiences obstacles in terms of digital skills and limited existing human resources. This study recommends utilizing social media actively and continuously, so that there is integration with online motorcycle taxi services, and to conduct digital marketing training.